“Let Mrs Mafekeng stay”: An evaluation of the Paarl riots of 1959 (Historia, 2021)
In South African historical research, the Paarl riots of 9-10 November 1959 have been viewed fleetingly as an episode centred around Elizabeth Mafekeng,1 a trade union activist of the 1940s and 1950s. On closer examination, however, most of theparticipants in the events, Coloured people,2 seem to have drawn to them for multifaceted reasons which question assigning their cause to the banishment of Mafekeng alone. The Cape Times, Cape Argus, New Age, Die Burger and Paarl Postnewspapers were examined for information concerning the riots. The Paarl Magistrate’s Criminal Records also provided insight into the nature of the unrest, while secondary literature concerning the Coloured population was also studied. The basis of the involvement of local inhabitants in the events was found to have been divided. Their participation could not be pinned down to one person or a single cause. Instead, a depiction and investigation of the full account of the events reveals three main groups that could be identified within their collective body. There were those who were actively involved; those who consciously separated themselves from the proceedings; and those whose participation did not seem to be politically motivated. The events appear to be more complex than they have been remembered.
Keywords: Elizabeth Mafekeng; Paarl; protest; African National Congress (ANC); apartheid